Multiple intelligence based tasks for enhancing reading motivation of university students in Ethiopia - Gebremeskel, Teshale Alemu; Bachore, Mebratu Mulatu; Bushisso, Elias Woemego (Institute of Advanced Engineering and Science, 2025)
The purpose of the study was to investigate the effectiveness of multiple intelligence-based tasks in enhancing students’ motivation towards reading. It employed a quasi-experimental design. A total of 60 communicative English class university students, who were selected purposefully participated as treatment and comparison groups. The research process was carried out with reading tasks that were designed based on a model for teaching using multiple intelligence-driven tasks for the treatment group while the comparison group followed the conventional approach for 12 weeks. English-reading motivation questionnaires and focused group discussions were used to gather data. Data normality check was carried out using Shapiro-Wilk tests, and a p value of 0.05 was used to determine the level of significance. T-tests were used to compare the scores between the two groups. It was found that multiple intelligence-based reading tasks (MIBRT) brought a significant difference in the students’ motivation, with the effect size value ranging from low (for importance), moderate (for efficacy and for extrinsic), and strong (for intrinsic). It was suggested that university teachers should use multiple intelligence-driven reading tasks as an alternative scaffolding tools to raise the motivational levels of struggling readers in the context of the study.